A new species of the genus Scutiger (Anura: Megophryidae) from Medog of southeastern Tibet, China - JIANG, Ke (Dongwuxue Yanjiu, 2016)
A new species of Scutiger Theobald, 1868 is described from Medog, southeastern Tibet, China, based on morphological and molecular data. The new species was previously identified as Scutiger nyingchiensis, but it can be differentiated from the latter and all other congeners by the following combination of characters: (1) medium adult body size, SVL 50.5-55.6 mm in males and 53.8-57.2 mm in females; (2) maxillary teeth absent; (3) web rudimentary between toes; (4) prominent, conical-shaped tubercles on dorsal and lateral surfaces of body and limbs; (5) tubercles covered by black spines in both sexes in breeding condition; (6) a pair of pectoral glands and a pair of axillary glands present and covered by black spines in males in breeding condition, width of axillary gland less than 50% of pectoral gland; (7) nuptial spines present on dorsal surface of first and second fingers, and inner side of third finger in males in breeding condition; (8) spines absent on the abdominal region; (9) vocal sac absent. In addition, the distribution and conservation status of the new species are also discussed.